Input management for precision farming in banana - Shimi G J (Department of Agronomy, College of Agriculture, 2014)
The investigation entitled “Input management for precision farming in banana” was carried out for two years (2012-2014) in Instructional Farm, College of Agriculture, Vellayani. The objectives were to study the impact of precision land management, fertigation and foliar nutrition on the growth and yield of tissue culture banana (Musa AAB cv. Nendran), to standardize the nutrient concentration and nutrient sources for fertigation and to work out the economics. The experiment was undertaken in two parts. In part I, standardization of nutrient sources for fertigation was carried out in factorial CRD with six nutrient sources [urea, Muriate of Potash (MOP), 10-10-10, 13-0-45, SOP (Sulphate of Potash), and Diammonium Phosphate (DAP)] and four concentrations (0.25, 0.50, 0.75 and 1.00 per cent), replicated thrice. In part II, nutrient scheduling was standardized in split plot design with six main plots and three sub plots in three replications. Main plot treatments were n1-POP (Package of Practices) with basin irrigation, n2-POP with drip irrigation, n3-drip irrigation alone without fertilizer, n4-soil application of rock phosphate and fertigation using urea and MOP, n5- fertigation using 10-10-10, urea and Sulphate of Potash (SOP) and n6- fertigation using 13-0-45, 0-0-50 and DAP. The sub-plot treatments were water spray (s1), foliar application of 19-19-19 @ 0.50 per cent [2, 4 and 6 MAP (Months After Planting)] (s2) and bunch spray with 2 per cent SOP (after complete bunch emergence and three weeks after first application) (s3). The general practices such as deep ploughing (50 cm), taking raised beds (30 cm height, 3 m width) and organic manure application (15 kg plant-1) were uniformly followed. Daily water requirement for drip irrigation was calculated using the formula suggested by FAO (1998). Separate sub mains were laid out for irrigating each treatment and fertigation was done using ventury. The concentrations tested revealed no phytotoxic effect on plants. Nutrient sources had significant influence on growth, yield and quality of banana. Growth parameters showed varying effect due to nutrient sources. During both the years, n1, n2, n4 and n5 registered higher yield which were on par and significantly superior to other sources. But in pooled analysis, n1, n2 and n4 recorded significantly higher yield of 32.55, 31.69, 31.58 t ha-1, respectively which were on par. Quality parameters also responded differently to nutrient sources and irrigation. The effect of foliar application on growth, yield and quality was also significant. Bunch spray with 2 per cent SOP significantly improved growth, yield and quality aspects. Input use efficiency also showed significant variation due to treatments. Among the nutrient sources and irrigation, the highest nutrient use efficiency (NUE) was registered by n4. Whereas in water productivity (WP), n2 was found superior and was on par with n4 in second year. Water use efficiency (WUE) was enhanced in n2 which was on par with n4 and n5 in first year. In second year, n4 was on par with n2, n5 and n6. NUE, WUE and WP were also significantly enhanced by s3. Compared to basin irrigation, fertigation resulted in a saving of 73 per cent in irrigation water and 40 per cent in nutrients. Significantly higher B : C ratio of 5.07 and 3.99 were registered by n4 and s3. The nutrient schedule standardized for precision farming in banana can be summarized as:- basal application of organic manure @ 15 kg plant-1, soil application of rock phosphate @ 325 g plant-1 (1 MAP) and @ 250 g plant-1 (3 MAP), weekly fertigation using urea @ 16.30 g plant-1 from 1 to 7 MAP (except 6 MAP) and MOP @ 16.25 g plant-1 from 1 to 5 MAP and @ 31.25 g plant-1 (7 MAP) along with bunch spray of 2 per cent SOP (after complete bunch emergence and three weeks after first application) or foliar spray of 0.50 per cent 19-19-19 (2, 4 and 6 MAP). This schedule along with improved land management practices of deep ploughing (50 cm deep) and taking raised beds (30 cm height) is beneficial for productivity enhancement in banana.